2010
DOI: 10.1016/j.jcrs.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of posterior capsule opacification models 2 years postoperatively with 2 single-piece acrylic intraocular lenses

Abstract: Eyes with an IOL with a continuous 360-degree square edge had significantly less PCO than eyes with an IOL with a square edge that was interrupted at the optic-haptic junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
2
27
4
1
Order By: Relevance
“…This could cause a loss of barrier function to migrating lens epithelial cells, which may worsen PCO inhibition. [25][26][27][28] In the present study, there was no significant difference in PCO from 3 to 5 years after surgery. We believe that the existing migratory lens epithelial cells at the optic-haptic junction or beneath the IOL optic create a tight barrier effect against the posterior capsule preventing the migration of lens epithelial cells towards central visual axis.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 53%
“…This could cause a loss of barrier function to migrating lens epithelial cells, which may worsen PCO inhibition. [25][26][27][28] In the present study, there was no significant difference in PCO from 3 to 5 years after surgery. We believe that the existing migratory lens epithelial cells at the optic-haptic junction or beneath the IOL optic create a tight barrier effect against the posterior capsule preventing the migration of lens epithelial cells towards central visual axis.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 53%
“…This is in marked contrast to the control IOLs, which showed a large amount of proliferative cortical material anteriorly and posteriorly with significant ACO and PCO, the latter starting at the optic-haptic junctions. This is especially remarkable because the control IOL was chosen for its uninterrupted 360-degree barrier edge; results in a clinical study 25 showed that the uninterrupted 360-degree barrier edge led to significantly less PCO than a 1-piece interrupted-edge hydrophobic acrylic IOL 2 years after implantation. Modifications of the current design of the study IOL to further reduce capsular bag opacification were proposed, and additional rabbit studies are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the posterior capsule acts as a substrate for the ingrowth of cells and fibrosis, leading to PCO and often to a significant secondary vision loss. The most common treatment for PCO is neodymium:yttrium-aluminium-garnet (Nd:YAG) laser capsulotomy to restore a clear visual axis (Nixon & Woodcock 2011). PCO has been subject to much research, and several potential causes have been identified.…”
Section: Introductionmentioning
confidence: 99%